Pengaruh Latihan Yoga Terhadap Peningkatan Keseimbangan Dinamis Pada Lanjut Usia - Akbar, Ega Doviana, Totok Budi Santoso, S.Fis, S.Pd, M.Ph, Maskun Pudjianto, SMPh., S.Pd., M.Kes (2016)
Background : is that Aging is a natural process it does not seem striking that is occur naturally. The changing of Muskuloskeletal in the elderly is cause of the decreasing number of muscle fibers resulting in decreased dynamic balance. Objective : is to determine the effect of yoga exercise to increase the dynamic balance in elderly patients. Method : that use is quasi experimental study with pre and post test design control groups. By comparing the balance of the time up and go test between the treatment group and the control groups were done for 4 weeks with a large sample of 24 respondents. The data analysis technique using the wilcoxon test for influence and man Whitney test for different test influences. Result : is that the result of dynamic balance in the treatment group obtained significant result, namely p=0.002 or p< 0.05. While the result of dynamic equilibrium in control group p = 0,209 or p < 0,06. Conclusion : yoga exercise influence on the dynamic balance of elderly in the treatment group was given the practice of yoga with the control group were not giving any treatment. Keywords: elderly, dynamic balance, yoga exercise